2023
DOI: 10.3390/biomedicines11020642
|View full text |Cite
|
Sign up to set email alerts
|

Immune Recognition versus Immune Evasion Systems in Zika Virus Infection

Abstract: The reemergence of the Zika virus (ZIKV) infection in recent years has posed a serious threat to global health. Despite being asymptomatic or mildly symptomatic in a majority of infected individuals, ZIKV infection can result in severe manifestations including neurological complications in adults and congenital abnormalities in newborns. In a human host, ZIKV is primarily recognized by RIG-like receptors and Toll-like receptors that elicit anti-viral immunity through the secretion of type I interferon (IFN) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 149 publications
0
6
0
Order By: Relevance
“…For genetic susceptibility studies in teratogenesis, it is important to select genes that are expressed and play a role during the development of the affected organs/structures. AXL , TLR3 , and STAT2 are expressed in different neural cells (Chan et al, 2023; Chen et al, 2018; Grant et al, 2016; Hastings et al, 2019; Liu et al, 2019; Meertens et al, 2017; Nowakowski et al, 2016; Ojha et al, 2019) and play roles on neurodevelopment during both embryonic and fetal periods (Ackerman, 1992). These characteristics make them good candidates of investigation on its participation on the occurrence of CZS regardless of the moment of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For genetic susceptibility studies in teratogenesis, it is important to select genes that are expressed and play a role during the development of the affected organs/structures. AXL , TLR3 , and STAT2 are expressed in different neural cells (Chan et al, 2023; Chen et al, 2018; Grant et al, 2016; Hastings et al, 2019; Liu et al, 2019; Meertens et al, 2017; Nowakowski et al, 2016; Ojha et al, 2019) and play roles on neurodevelopment during both embryonic and fetal periods (Ackerman, 1992). These characteristics make them good candidates of investigation on its participation on the occurrence of CZS regardless of the moment of infection.…”
Section: Discussionmentioning
confidence: 99%
“…STAT2 activation triggers the expression of several IFN‐stimulated genes (ISGs) to suppress the infection (MacMicking, 2012). Additionally, studies have also shown that the NS5 protein of ZIKV binds and degrades the human STAT2, via the proteasome, inhibiting the IFN signaling and allowing ZIKV infection and viral dissemination to the central nervous system (Chan et al, 2023; Grant et al, 2016; Hertzog et al, 2018; A. Kumar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…112,113 These assessments go into certain viral details in greater detail. 114 process (Table 1). However, only a small part of them have access to clinical research and applications.…”
Section: Evasion Of Antiviral Innate Immune Recognition By Viral Rna ...mentioning
confidence: 99%
“…24 A study has witnessed an elevation in Zika virus replication due to I39T mutation in the NS2B protein and A188V mutation in NS1 gene has augmented virulence by escalating the antigenicity of the NS1 protein. 25 Chen et al have reported E92Q and N155H mutations in HIV-1 integrase, which has altered its binding with elvitegravir drug. 26 Another study has reported that Q148H/R and G140S/A caused resistance to ratlegravir drug, and molecular dynamic (MD) simulation has shown that mutant models are less flexible than wild-type, as a result the susceptibility to drug in patients have been reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A single‐point mutation (R292K) in neuraminidase protein of H7N9 virus led to oseltamivir drug resistance often used for treating influenza 24 . A study has witnessed an elevation in Zika virus replication due to I39T mutation in the NS2B protein and A188V mutation in NS1 gene has augmented virulence by escalating the antigenicity of the NS1 protein 25 . Chen et al.…”
Section: Introductionmentioning
confidence: 99%